2021
DOI: 10.1007/s40261-021-01046-1
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1 Study to Evaluate the Drug Interaction Between Islatravir (MK-8591) and Doravirine in Adults Without HIV

Abstract: Background and Objectives Islatravir (MK-8591) is a novel nucleoside analogue in development for the treatment and prevention of HIV-1 infection. Doravirine is a non-nucleoside reverse transcriptase inhibitor indicated for the treatment of HIV-1 infection. This study evaluated the pharmacokinetics, safety, and tolerability of islatravir and doravirine coadministration in a double-blind, placebo-controlled, randomized, fixed-sequence study. Methods Adult participants without HIV infection were administered oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Based on previous preclinical and clinical PK data, plasma islatravir and PBMC islatravir-TP levels were expected to increase in participants with severe RI relative to healthy control participants, considering islatravir undergoes renal clearance ( 6 , 12 , 13 , 23 , 25 ). The results of the current study suggest that plasma islatravir and M4 exposure were, in fact, higher in participants with severe RI, consistent with renal excretion as a relatively major factor in islatravir elimination ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous preclinical and clinical PK data, plasma islatravir and PBMC islatravir-TP levels were expected to increase in participants with severe RI relative to healthy control participants, considering islatravir undergoes renal clearance ( 6 , 12 , 13 , 23 , 25 ). The results of the current study suggest that plasma islatravir and M4 exposure were, in fact, higher in participants with severe RI, consistent with renal excretion as a relatively major factor in islatravir elimination ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…This lack of inhibition and/or induction of major drug-metabolizing enzymes as well as common hepatic cotransporters (OATP1B1, OATP1B3, OCT1) allow for co-administration of other antiretrovirals with ISL. Furthermore, a phase 1b study analyzed the impact of ISL on the pharmacokinetic profile of the NNRTI doravirine in adults without HIV infection [40] and found that the pharmacokinetic of doravirine administered alone and in combination with ISL were comparable and that doravirine did not have a meaningful impact on the pharmacokinetic of ISL. Similarly, a study of 14 healthy subjects found no clinically meaningful interaction between ISL and the investigational NNRTI MK-8507 [41].…”
Section: Drug-drug Interactionsmentioning
confidence: 99%